Effect of different solvents extraction on antioxidant and alpha glucosidase inhibitory activity of Ipomoea aquatica cultivars - Lawal, Umar; Shaari, Khozirah; Ismail, Intan Safinar; Khatib, Alfi; Abas, Faridah (2015)
Antioxidant play an important role in inhibiting and scavenging free radicals, thus providing protection to human against infections and degenerative diseases. Ipomoea aquatica Forsk is a green leafy vegetable that is a rich source of vitamins and amino acids with many health benefits. The present study was designed to investigate the effect of using water and methanol at different ratio on the total phenolics, antioxidant capacity and alpha-glucosidase inhibitory of three types of I. aquatica cultivar. The results revealed that 70% methanol extract of K-11 showed higher alpha-glucosidase inhibory and antioxidant activity compare to the other two cultivars. Identification of phytochemical constituents in the active extract (K-11) was carried out by LC-DAAD-ESIMS/MS) reveal the presence of quesrcetin-3-O-sophoroside, quercetin-3-glucosides, 4,5-di-O-caffeoylquinic acid, 3,5-di-O-caffeoylquinic acid, luteolin-7-glucoside and 3,4,5-tricaffeolquinic acid. The identity of the compounds was confirmed by isolation and spectroscopic evidences together with comparison with literature data. This study indicates that 70% methanol is the most efficient solvent for the extraction of polyphenolic compounds from I. aquatica.